2011
DOI: 10.1161/circimaging.109.895607
|View full text |Cite
|
Sign up to set email alerts
|

MRI of Coronary Wall Remodeling in a Swine Model of Coronary Injury Using an Elastin-Binding Contrast Agent

Abstract: Background-The extracellular matrix (ECM) plays an important role in the pathogenesis of atherosclerosis and in-stent restenosis. Elastin is an essential component of the ECM. ECM degradation can lead to plaque destabilization, whereas enhanced synthesis typically leads to vessel wall remodeling resulting in arterial stenosis or in-stent restenosis after stent implantation. The objective of this study was to demonstrate the feasibility of MRI of vascular remodeling using a novel elastin-binding contrast agent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 40 publications
3
51
0
Order By: Relevance
“…23 Gd-ESMA has been successfully applied to assess atherosclerotic plaque burden in a model of apolipoprotein E-deficient mice, 6 as well as to investigate arterial wall remodeling after stent placement in a swine model of coronary injury. 24 Preliminary data have also suggested that Gd-ESMA may be suitable for the quantification of elastin in liver fibrosis. 25 Although no specific toxicity studies for Gd-ESMA were performed yet, the previous reports published on Gd-ESMA, as well as our study, did not report any adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…23 Gd-ESMA has been successfully applied to assess atherosclerotic plaque burden in a model of apolipoprotein E-deficient mice, 6 as well as to investigate arterial wall remodeling after stent placement in a swine model of coronary injury. 24 Preliminary data have also suggested that Gd-ESMA may be suitable for the quantification of elastin in liver fibrosis. 25 Although no specific toxicity studies for Gd-ESMA were performed yet, the previous reports published on Gd-ESMA, as well as our study, did not report any adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by von Bary et al, pigs with injury to the coronary wall by endothelial denudation or stent placement were imaged using a novel elastinbinding MR contrast agent, designated BMS-753951 (85). Delayed enhancement using BMS-753951 showed a 3-fold higher contrast-to-noise ratio in the stented coronary artery than in the balloon-injured or control (uninjured) artery, whereas gadolinium-DTPA showed only minor or no late enhancement.…”
Section: Advanced Molecular Imaging Applicationsmentioning
confidence: 99%
“…Furthermore, the clearance of the contrast agent is comparable 27 to approved gadolinium-based MR contrast agents allowing for early imaging after injection with minimal background signal and thus maximal target to blood contrast to noise. The high-resolution DE-MRI and the T1 mapping sequences we developed and used are directly applicable to large animal models 42 and humans with an even higher expected accuracy and specificity due the ≈10 to 20 times greater arterial wall thickness and consequently higher elastin content.…”
Section: Translational Potential Of Esmamentioning
confidence: 99%